2006
DOI: 10.1097/01.paf.0000203269.97907.a7
|View full text |Cite
|
Sign up to set email alerts
|

Choking on Toilet Paper

Abstract: While reports of suicide by smothering and strangulation are common, suicide by choking is far more rare. In addition to the act being difficult to carry out, suspected cases are not easily distinguished from accidental or homicidal deaths. Here, we present a case of suicide by choking on toilet paper in a patient with a long history of schizophrenia. The case was ruled a suicide based on the patient having been witnessed in a previous unsuccessful attempt of the same act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The manner of death can be classified as accidental (Francis et al 2013), homicidal (Kurihara et al 1992;Kitulwatte and Edirisinghe 2020), or attributed to suicide (Pampin and Varela 2001;Sauvageau and Yesovitch 2006). Psychiatric disorders are associated with suicide, while abuse of drugs and alcohol has been associated with accidental death resulting from choking.…”
Section: Discussionmentioning
confidence: 99%
“…The manner of death can be classified as accidental (Francis et al 2013), homicidal (Kurihara et al 1992;Kitulwatte and Edirisinghe 2020), or attributed to suicide (Pampin and Varela 2001;Sauvageau and Yesovitch 2006). Psychiatric disorders are associated with suicide, while abuse of drugs and alcohol has been associated with accidental death resulting from choking.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports indicated suicide by mechanical asphyxia using toilet paper: one patient suffering from schizophrenia (Sauvageau & Yesovitch, 2006) and another patient with borderline personality disorder (Saint-Martin, Bouyssy & O'Byrne, 2007). It is not always easy to distinguish suicide from homicide, and another study reported the case of a homicide by toilet paper smothering in a patient with Alzheimer's disease (Saint-Martin, Lefrancq & Sauvageau, 2012).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…paranoid personality disorder, psychotic disorders). In a patient with depressive mood, suicidal ideation needs to be explored because toilet paper might be used as a lethal mechanism for committing suicide (Sauvageau & Yesovitch, 2006;Saint-Martin, Bouyssy & O'Byrne, 2007).…”
Section: Managing Toilet Paper Hoarding: a Proposed Algorithm From The Catotim Groupmentioning
confidence: 99%
“…Interestingly, with only two applications of transcranial alternating current stimulation (tACS), the patient showed immediate improvement (using less than one toilet roll per day). Two case reports indicated suicide by mechanical asphyxia using toilet paper: one patient suffering from schizophrenia (Sauvageau & Yesovitch, 2006) and another patient with borderline personality disorder (Saint-Martin, Bouyssy & O'Byrne, 2007). It is not always easy to distinguish suicide from homicide, and another study reported the case of a homicide by toilet paper smothering in a patient with Alzheimer's disease (Saint-Martin, Lefrancq & Sauvageau, 2012).…”
Section: Systematic Reviewmentioning
confidence: 99%